2006
DOI: 10.1063/1.2222041
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the charge transport through disordered organic molecular heterojunctions

Abstract: We develop a new three-dimensional multiparticle Monte Carlo (3DmpMC) approach in order to study the hopping charge transport in disordered organic molecular media. The approach is applied here to study the charge transport across an energetically disordered organic molecular heterojunction, known to strongly influence the characteristics of the multilayer devices based on thin organic films. The role of energetic disorder and its spatial correlations, known to govern the transport in the bulk, are examined he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 45 publications
(45 reference statements)
0
49
0
Order By: Relevance
“…Therefore, it is important to study the effects of Coulomb interactions in devices where high carrier densities can be reached at the electrodes in the case of low injection barriers and where the carrier density can vary over several orders of magnitude within a distance of only a few nanometers from the electrodes. The effect of Coulomb interactions on transport across organic heterojunctions has been studied using MC simulations by Houili et al 23 At these heterojunctions the carrier concentration can also become very large, leading to important effects of Coulomb interactions. Multiparticle MC simulation methods have also been used to study diffusion-limited recombination in polymer-fullerene blends.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to study the effects of Coulomb interactions in devices where high carrier densities can be reached at the electrodes in the case of low injection barriers and where the carrier density can vary over several orders of magnitude within a distance of only a few nanometers from the electrodes. The effect of Coulomb interactions on transport across organic heterojunctions has been studied using MC simulations by Houili et al 23 At these heterojunctions the carrier concentration can also become very large, leading to important effects of Coulomb interactions. Multiparticle MC simulation methods have also been used to study diffusion-limited recombination in polymer-fullerene blends.…”
Section: Introductionmentioning
confidence: 99%
“…Although one has to be careful to ensure that charges are not double-counted [129], this approach allows one to trade-off speed and the accuracy of long-range Coulomb interactions through choice of rc. An advantage of this approach is that it is possible to maintain the full accuracy of short range Coulomb interactions, which have been shown to assist detrapping of charge [129] and hence have a significant effect on predicted current [121]. Still further gains in efficiency are possible by borrowing ideas from interacting particle simulations.…”
Section: Computational Efficiencymentioning
confidence: 99%
“…Arkhipov et al [120] showed using a KMC model that one cannot simply model the process as thermionic emission over a potential barrier due to a 'backflow' of charges which depends on electric field and potential barrier. Houlli et al [121] demonstrated that that a 1D continuum approach significantly overestimates the effect of Coulomb interactions on current passing a heterojunction due to the effect of energetic disorder. This is inconvenient from a modelling perspective since DD models are computationally efficient, particularly at the large charge densities found in OLEDs.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…The Marcus model [40,41] and the Miller-Abrahams [42] model provide insight into how to calculate the hopping rates and macroscopic properties of charge transport in such disordered systems. The theoretical value of charge mobility can be derived by Monte Carlo simulations [43] or hopping master equations [44]. Charge mobilities can also be determined by various experimental techniques, such as time of flight (TOF) [41][42][43], space charge limited current (SCLC) [45][46][47], and source-drain current versus gate voltage in field effect transistors (FETs) [48,49].…”
Section: Mobility Measurementsmentioning
confidence: 99%